Large Displacements and the Stiffness of a Flexible Shell. Issue 3 (December 2015) - Charpentier, Victor; Adriaenssens, Sigrid; Baverel, Olivier
The design of static thin shell structures can be carried out using analytical and numerical approaches. Recently, thin shells have been studied for their flexibility, which can be beneficial for adaptive systems. However flexible systems involve large displacements and precise kinematics. The analysis of flexible shell systems is challenging due to the nonlinearities induced by these large displacements. This study addresses the nonlinear behaviour and stress-stiffening effects caused by large displacements in a 0.80 m-long carbon fibre reinforced plastic shell consisting of two monolithically connected lobes. The structural behaviour of this system is investigated both numerically and experimentally. Following the analysis framework, the non-linear effects of the large displacements on the shell stiffness are numerically determined using eigenvalue analysis and the displacement response to external loading on deformed shell configurations. The numerical displacement results are compared with results obtained in the experimental study. In conclusion, our study shows that the stiffness of the shell system under study increases 113% during deformation. More precisely, we establish that this change in stiffness is governed by the presence of tensile stresses in the shell surface due to deployment rather than by the change of the system's geometry.